Law on the conclusion, accession to and implementation of treaties - The National Assembly (2005)
This Law provides for the conclusion, accession, reservation, deposit, keeping custody, making of certified copies, publication, registration, implementation, interpretation, amendment, supplementation, extension, termination, denunciation, withdrawal, suspension of application of treaties concluded or acceded to in the name of the State or the name of the Government of the Socialist Republic of Vietnam